Community Participation in Development of Ecotourism in Taman Beach, Pacitan District - Putra, Heru Wiwoho Supadi; Hakim, Abdul; Riniwati, Harsuko; Leksono, Amin Setyo (Graduate School, Universitas Brawijaya, 2019)
Taman Beach as one of the superior tourist destinations in Pacitan has now begun to develop. The development of Taman Beach tourism object is inseparable from the efforts which are initiated by the Group of Turtle Rescue Society for Tourism